Prognostic factors in locally advanced oesophageal squamous cell carcinoma: a clinical and radiomic analysis of neoadjuvant immunochemotherapy before surgery - Zhu, Yan; Zhang, Zhenzhong; Chen, Shuangqing; Bai, Genji; Xu, Qingqing; Zhang, Lili; Gao, Max; Ruan, Aichao; Guo, Lili (Frontiers in Oncology, 2025)
BackgroundThe treatment of locally advanced oesophageal squamous cell carcinoma (LAESCC) without distant metastasis remains a subject of debate. Neoadjuvant immunochemotherapy (NIC) combined with surgery is the preferred initial approach for managing LAESCC. However, information on the clinical efficacy and survival of patients with LAESCC treated with NIC followed by surgery is limited.MethodsThis retrospective analysis aimed to identify predictors NIC treatment effectiveness and on patient survival. We developed a Cox proportional hazards model and Kaplan–Meier curve to estimate progression-free survival (PFS) and overall survival (OS) following NIC treatment and surgery.ResultsOverall, 225 patients with LAESCC were divided into training (157) and test set (68) (7:3). After a median follow-up of 2.86 years, death was observed as a positive event in 41 patients (26.1%). It is statistically significant to construct a prediction model combining radiomics features pre- and post-NIC with clinical features to predict the PFS and OS of LAESCC. The combined model showed the highest performance in predicting both disease-free survival and OS compared with the clinical or radiomics models. multivariate Cox regression analysis identified smoking (HR = 1.417, 95% confidence interval [CI]: 0.875–2.293, p = 0.156), Ki67(HR = 2.426, 95% confidence interval [CI]: 1.506–3.908, p = 0.000) and postRad-S1 (HR = 1.867, 95% CI: 1.053–3.311, p = 0.033) as significant independent covariates associated with high PFS. While Ki67 and postRad-S2 were prognostic factors significantly associated with OS (HR = 1.521, 95% CI: 0.821–2.818, p = 0.183; HR = 1.912, 95% CI: 1.001–3.654, p = 0.050, respectively).ConclusionFor patients with LAESCC treated with NIC followed by surgery, the combined model effectively evaluated the efficacy of NIC and predicted PFS and OS. Additionally, different independent predictors were associated with PFS and OS, providing clues for future studies.